The influence of delay factors on Pahang Malaysian construction industry: A PLS-SEM approach - Adeleke, A. Q.; Adeniyi, A. W.; Muuka, G. N. (Penerbit Universiti Malaysia Pahang, 2021)
Previous research has shown that delay is a common problem in construction industry. Weather condition and regulation changes, though being minor factors, are also known as external factors contributing to the delay of project construction. This study involved 118 respondents from the construction industry in Kuantan, Pahang. In order to obtain the data, copies of questionnaire were distributed widely among people in Pahang construction industry. The data were analysed by using Partial Least Squares Structural Equation Modelling version 3. A significant positive relationship between weather conditions and building projects in Pahang construction industry was identified. This study also found a negative relationship between regulation changes and building projects in Pahang construction industry. As expected, weather conditions were found to be one of the factors contributing to delay in the process of projects’ construction in Malaysia. However, weather conditions and the regulation changes did not significantly affect the construction projects in Malaysia. Out of the factors which contributed to delay in building projects, weather conditions, though a minor factor, played to an extent a part in contributing to extension of the time of the projects in Malaysia. Nevertheless, regulation changes was not considered a vital factor leading to delay in building projects in Malaysia.